[D-Leu1]MC-LR Has Lower PP1 Inhibitory Capability and Greater Toxic Potency than MC-LR in Animal and Plant Tissues - Sedan, Daniela Yazmine (2020)
Two microcystins, MC-LR and [D-Leu1]MC-LR, present in La Plata Basin blooms, are differentiated by substitution of D-Alanine for D-Leucine at position 1. Our objective was to evaluate acute toxicity of [D-Leu1]MC-LR and MC-LR in mice (N:NIH Swiss) and beans (Phaseolus vulgaris). We observed variations in [D-Leu1]MC-LR lethal doses with respect to those reported for MC-LR (100 μg/kg), with an increased liver/body weight ratio and intrahepatic hemorrhages in mice exposed to 50–200 μg [D-Leu1]MC-LR/kg and slight steatosis after a single 25 μg [D-Leu1]MC-LR/kg i.p. dose. Our study in the plant model showed alterations in germination, development, morphology and TBARs levels after a single contact with the toxins during imbibition (3.5 and 15 µg/mL), those treated with [D-Leu1]MC-LR being more affected than those treated with the same concentration of MC-LR. Protein phosphatase 1 (PP1) IC50 values were 40.6 nM and 5.3 nM for [D-Leu1]MC-LR and MC-LR, respectively. However, the total phosphatase activity test in root homogenate showed 60% inhibition for [D-Leu1]MC-LR and 12% for MC-LR. In mouse liver homogenate, 50% inhibition was observed for [D-Leu1]MC-LR and 40% for MC-LR. Our findings indicate the need for further research into [D-Leu1]MC-LR toxicity since together with oxidative stress, the possible inhibition of other phosphatases could explain the differences detected in the potency of the two toxins.